Diagnóstico y mejora empresarial de la empresa comercial Karoda - Arredondo Caballero, María Jose (2021)
The following research work was carried out with the objective of diagnosing the Commercial Karoda company, to identify what the main problems are and take advantage of the strengths it has also finding the factors that limit the development of the company in future years. In Chapter 1 the areas of the company are presented, the products that it imports and sells, it is showed the VRIO analysis for its main product, which is synthetic leather. In Chapter 2, a preliminary diagnosis is made in which five main problems are chosen. In Chapter 3 the general and specific objectives, sources of information and the hypothesis are setted out, the hypotesis indicates that the main problem is in the area of operations. In chapters 4 and 5 the theoretical framework and the diagnosis of all the processes of the company are developed using the Thibaut method. Likewise, the main problem of the organization is selected, which is related to the commercial area and the operations area, critical areas in the company. In Chapter 6, various solutions to mitigate the root cause are proposed and compared to find the most urgent solution to implement. The design, development, implementation, and ways of monitoring the improvement are carried out, along with a schedule for the proposal. In Chapter 7 the evaluation of the improvement proposal is carried out, in which it is evaluated if the proposal would really provide benefits to the company. Finally, in Chapter 8 the main factors that would promote the development of the results according to the proposal.